2021
DOI: 10.3390/cells10123521
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Inhibits Tau Aggregation In Vitro

Abstract: A hallmark of Alzheimer’s disease (AD) is the accumulation of tau protein in the brain. Compelling evidence indicates that the presence of tau aggregates causes irreversible neuronal destruction, eventually leading to synaptic loss. So far, the inhibition of tau aggregation has been recognized as one of the most effective therapeutic strategies. Cannabidiol (CBD), a major component found in Cannabis sativa L., has antioxidant activities as well as numerous neuroprotective features. Therefore, we hypothesize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In addition to the amyloid β model, researchers have also investigated the effect of CBD in the tauopathy model of AD. Recently, Alali et al have reported that CBD can inhibit aggregation of tau protein ( Alali et al, 2021 ). Using in vitro and in silico biochemical methods such as circular dichroism (CD) and atomic force microscopy (AFM), the author has demonstrated that CBD molecules bind to recombinant human tau protein and inhibit its aggregation.…”
Section: Disease-specific Pathwaymentioning
confidence: 99%
“…In addition to the amyloid β model, researchers have also investigated the effect of CBD in the tauopathy model of AD. Recently, Alali et al have reported that CBD can inhibit aggregation of tau protein ( Alali et al, 2021 ). Using in vitro and in silico biochemical methods such as circular dichroism (CD) and atomic force microscopy (AFM), the author has demonstrated that CBD molecules bind to recombinant human tau protein and inhibit its aggregation.…”
Section: Disease-specific Pathwaymentioning
confidence: 99%
“…Plotting dbAF intensity at 456 nm against the incubation time gives rise to a typical sigmoid-like kinetic curve for the two C-TER isoforms ( Figure 6 A). Such a three-phase kinetic profile is well described in the literature and is characteristic of amyloidogenic proteins [ 77 , 78 ]. The lag phase, corresponding to structural transitions, nucleation, and assembly of oligomers, is nearly the same for the two proteins: 36 and 40 h for C-TERb and C-TERa, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…Generally, the tau exhibits intrinsic fluorescence emission near 302 nm when excited at 265 nm, resulted from tyrosine (Tyr) fluorophores in the tau structure. 48,49 When 10 μM of tau was mixed with GQDs or Cys-GQDs in increasing concentrations, the fluorescence intensity of tau was significantly quenched (Fig. 7), suggesting that the π-conjugated planar structure of GQDs binds with Tyr residues in tau, probably via π-π stacking interactions.…”
Section: Resultsmentioning
confidence: 99%